Characterizing early embryonic development of Brown Tsaiya Ducks (Anas platyrhynchos) in comparison with Taiwan Country Chicken (Gallus gallus domestics) - Lumsangkul, Chompunut; Fan, Yang-Kwang; Chang, Shen-Chang; Ju, Jyh-Cherng; Chiang, Hsin-I. (PloS one, 2018)
Avian embryos are among the most convenient and the primary representatives for the study of classical embryology. It is well-known that the hatching time of duck embryos is approximately one week longer than that of chicken embryos. However, the key features associated with the slower embryonic development in ducks have not been adequately described. This study aimed to characterize the pattern and the speed of early embryogenesis in Brown Tsaiya Ducks (BTD) compared with those in Taiwan Country Chicken (TCC) by using growth parameters including embryonic crown-tail length (ECTL), primitive streak formation, somitogenesis, and other development-related parameters, during the first 72 h of incubation. Three hundred and sixty eggs from BTD and TCC, respectively, were incubated at 37.2°C, and were then dissected hourly to evaluate their developmental stages. We found that morphological changes of TCC embryos shared a major similarity with that of the Hamburger and Hamilton staging system during early chick embryogenesis. The initial primitive streak in TCC emerged between 6 and 7 h post-incubation, but its emergence was delayed until 10 to 13 h post-incubation in BTD. Similarly, the limb primordia (wing and limb buds) were observed at 51 h post-incubation in TCC embryos compared to 64 h post-incubation in BTD embryos. The allantois first appeared around 65 to 68 h in TCC embryos, but it was not observed in BTD embryos. At the 72 h post-incubation, 40 somites were clearly formed in TCC embryos while only 32 somites in BTD embryos. Overall, the BTD embryos developed approximately 16 h slower than the chicken embryo during the first 72 h of development. To our best knowledge, this is the first study to describe two distinct developmental time courses between TCC and BTD, which would facilitate future embryogenesis-related studies of the two important avian species in Taiwan.